Determinan of Safety Riding on Gojek Rider Community at the Jember Regency - Azizah, Ulfiatul; Indrayani, Reny; Hartanti, Ragil Ismi (Universitas Airlangga, 2024)
Introduction: Safety riding is a behavior to minimize the level of danger as well as safety and security in riding that accordance with laws and regulations system in our country. Safety riding is very important, especially for online motorcycle taxi drivers who have a high risk of having a traffic accident at work. Gojek is one of the largest online transportation companies in Indonesia. Method: This research was conducted on Gojek driver partners in three sub-districts of the Jember urban areas Sumbersari, Patrang and Kaliwates. A study that aims to analyze factors related to safety riding on the Gojek Rider community in the urban area of Jember Regency. This study is a quantitative study using an observational analytical research type with a cross-sectional research design with a sample of 75 drivers. Data collection used interview instrument adopted from previous research, observations and documentations. Analysis of the correlation data used the Chi-Square test. Result: This research the majority of Gojek drivers had 2 years of service (72%), good riding knowledge (68%), mobile phone usages usage on the road without pulling over (74,7%), moderate work fatigue (64%), roadworthy vehicles (82.7%) and unsafe riding (61.3%). Conclusion: There is no correlation between length of service and safety riding. There is a correlation between driving knowledge, work fatigue, cell phone use and vehicle factors.